India : 2010 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, economic developments of India are discussed. Growth is among the fastest-growing in the world, social indicators are improving, and medium-term economic prospects are favorable. The Reserve Bank of India's (RBI) efforts are used to tighten monetary conditions. The measures taken to increase the availability of long-term finance for infrastructure, especially, are helping to develop the corporate bond market. Executive Directors commended the introduction of the RBI's financial stability report, the review of financial laws, and the creation of financial stability and development council.